Arginase 1 deletion in myeloid cells affects the inflammatory response in allergic asthma, but not lung mechanics, in female mice - Cloots, Roy H. E. (BMC Pulm Med, 2017)
BACKGROUND: (Over-)expression of arginase may limit local availability of arginine for nitric oxide synthesis. We investigated the significance of arginase1 (ARG1) for the development of airway hyperresponsiveness (AHR) and lung inflammation in female mice with ovalbumin (OVA)-induced allergic asthma. METHODS: Arg1 was ablated in the lung by crossing Arg1 (fl/fl) and Tie2Cre (tg/−) mice. OVA sensitization and challenge were conducted, and AHR to methacholine was determined using the Flexivent system. Changes in gene expression, chemokine and cytokine secretion, plasma IgE, and lung histology were quantified using RT-qPCR, ELISA, and immunohistochemistry, respectively. RESULTS: Arg1 ablation had no influence on the development of OVA-induced AHR, but attenuated OVA-induced increases in expression of Arg2 and Nos2, Slc7a1, Slc7a2, and Slc7a7 (arginine transporters), Il4, Il5 and Il13 (T(H)2-type cytokines), Ccl2 and Ccl11 (chemokines), Ifng (T(H)1-type cytokine), Clca3 and Muc5ac (goblet cell markers), and OVA-specific IgE. Pulmonary IL-10 protein content increased, but IL-4, IL-5, IL-13, TNFα and IFNγ content, and lung histopathology, were not affected. Arg1 elimination also decreased number and tightness of correlations between adaptive changes in lung function and inflammatory parameters in OVA/OVA-treated female mice. OVA/OVA-treated female mice mounted a higher OVA-IgE response than males, but the correlation between lung function and inflammation was lower. Arg1-deficient OVA/OVA-treated females differed from males in a more pronounced decline of arginine-metabolizing and -transporting genes, higher plasma arginine levels, a smaller OVA-specific IgE response, and no improvement of peripheral lung function. CONCLUSION: Complete ablation of Arg1 in the lung affects mRNA abundance of arginine-transporting and -metabolizing genes, and pro-inflammatory genes, but not methacholine responsiveness or accumulation of inflammatory cells. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12890-017-0490-7) contains supplementary material, which is available to authorized users.